De novo mutations of STXBP1 in Chinese children with early onset epileptic encephalopathy - Li, T.; Cheng, M.; Wang, J.; Hong, S.; Li, M.; Liao, S.; Xie, L.; Jiang, L. (Genes, brain and behavior, 2018)
To detect syntaxin‐binding protein 1 (STXBP1) mutations in Chinese patients with early onset epileptic encephalopathy (EOEE) of unknown etiology. Targeted next‐generation sequencing was used to identify STXBP1 mutations in 143 Chinese patients with EOEE of unknown etiology. A filtering process was applied to prioritize rare variants of potential functional significance. Then Sanger sequencing was employed to validate the parental origin of the variants. Detailed clinical and genetic data were collected for 9 STXBP1‐positive patients. Eight de novo heterozygous STXBP1 mutations were identified in 9 patients; 5 were novel mutations (c.1155delC, c.1030‐1G>A, c.217G>C, c.268G>C, c.1480_1481 insT) and 3 were previously reported (c.1216C> T, c.1217G>A [2 cases], c.875G>A). Two patients had Ohtahara syndrome and 1 had West syndrome at onset, whereas the other 6 presented with EOEE that did not fit a specific recognized epilepsy syndrome. Six of these patients later evolved to West syndrome. All but 2 cases were prescribed more than 2 antiepileptic drugs (AEDs) plus other regimens. Four subjects showed good responses to levetiracetam (LEV) alone or in combination with other AEDs, and one case (1/3) achieved complete freedom from seizures with a ketogenic diet (KD). All patients exhibited severe to profound global developmental delay. Five novel heterozygous de novo STXBP1 mutations were discovered in patients with EOEE from China. STXBP1 mutational analysis should be performed in cases of EOEE of unknown etiology. LEV as monotherapy or adjunctive therapy with other regimens, as well as KD should be considered for management of this patient group. Five novel heterozygous de novo syntaxin‐binding protein 1 (STXBP1) mutations were discovered in patients with early onset epileptic encephalopathy (EOEE) from China. The figure shows the summary of the STXBP1 mutations.